Outstanding heritage sites, a resource for the territories - Magali Talandier; Françoise Navarre; Jean-François Ruault; Laure Cormier; Associate Professor; Pierre-Antoine Landel; Nicolas Senil (Via@)
In their host territories, outstanding heritage sites condense stakes of economic development, financial management, governance, appropriation and preservation of heritage. Both a source of attractiveness and a cause of tensions, what are the local socio-economic impacts that can be expected from these exceptional sites, such as those that are members of the Grands Sites de France network or those listed as UNESCO World Heritage Sites? To answer this question, the paper mobilizes the notion of territorial resource, in order to apprehend the impact of the site with regard to the territorial context and the coordination of local actors. Based on a quantitative and qualitative study carried out in France, the results highlight the existence of at least three types of impacts and processes. Outstanding sites can be either an ordinary resource, which accentuates dynamics or conflicts depending on the case; or a latent resource, lacking activation; or finally a powerful lever for local transformation. Far from the expected heritage miracle, these analyses show to what extent coordination between public and private actors is essential in order to turn heritage into a real resource for the territories.